General Election Debates – Problems and Solutions - Vella, Trina (HAPSc Policy Briefs Series, 2020)
Pre-election debates are one of the most important steps in the electoral process – indeed, they serve an important public interest as they inform the American public about the issues of the day and offer a forum by which candidate proposed solutions may be heard. However, pre-election debates are led by moderators who generally do not have expertise in many of their key topic areas, such as law or judicial studies; and because of this, the propositions and arguments made by candidates in the pre-election time may be de-contextualized during debates such that the voting public may be misled in terms of the practicality of candidate positions. It is not unusual for individuals to unwittingly make propositions which insufficiently account for the confines of governmental structures, norms, and institutions in important ways. Likewise, it is not expectable for candidate to have absolute expertise in all areas of the debate, such as from health care to international law. This presents a real and pressing problem or issue for the quality of debates and democracy. It would be useful for pre-election debates to have additional facilitators present to provide basic factual and scientific information, as well to define key terms and principles relevant to American government and political life. Thus, given the current format of pre-election debates, this policy brief offers proposals to increase voter awareness and thus strengthen American democracy through amendments to the pre-election debate format for general elections.